Role of Citrullinated Fibrinogen Peptides in the Activation of CD4 T Cells from Patients with Rheumatoid Arthritis - Shin, Kihyuk; Hong, SeokChan; Choi, Eun-Hye; Lim, Mi-Kyoung; Shim, Seung-Cheol; Ju, Ji-Hyeon; Lee, Seung-Hyo (Immune network, 2013)
This study was conducted to determine whether CD4 T cell responses to citrullinated fibrinogen occur in patients with rheumatoid arthritis (RA), especially in HLA-DR4-positive subjects. Whole peripheral blood mononuclear cells (PBMCs) of RA patients and control subjects were stimulated with citrullinated fibrinogen peptides, and T-cell production of proliferation and proinflammatory cytokines, such as interferon-γ(IFN-γ) and interleukin-17A (IL-17A), were measured. In addition, CD4 T cells from RA patients were stimulated with the citrullinated fibrinogen peptide, Fib-α R84Cit, identified as a DRB1(*)0401-restricted T cell epitope in HLA-DR4 transgenic mice, and the degree of T cell activation was examined similarly. No proliferative responses to the citrullinated fibrinogen peptides were observed in whole PBMCs or CD4 T cells from RA patients. Furthermore, no increased production of IFN-γ or IL-17A was found in whole PBMCs or CD4 T cells stimulated with the citrullinated fibrinogen peptides, although these cells responded to recall antigen, a mixture of tetanus toxoid, purified protein derivative (PPD) from Mycobacterium tuberculosis, and Candida albicans. The results of this study indicate that anti-citrulline immunity in RA patients may be mediated by fibrinogen because there is no evidence of CD4 T cell-mediated immune responses to citrullinated fibrinogen peptides.